Secreted Rv1768 From RD14 of Mycobacterium tuberculosis Activates Macrophages and Induces a Strong IFN-γ-Releasing of CD4+ T Cells - Yuan, Chun-Hui; Zhang, Simin; Xiang, Feiyan; Gong, Hongjian; Wang, Qian; Chen, Yan; Luo, Wei (Frontiers in Cellular and Infection Microbiology, 2019)
As the first line defensive mediators against Mycobacterium tuberculosis (M. tb) infection, macrophages can be modulated by M. tb to influence innate and adaptive immunity. Recently, we have identified several potential immunodominant T-cell antigens from the region of deletion (RD) of Mycobacterium tuberculosis (M. tb) H37Rv, including Rv1768 from RD14. In this study, we further determined that Rv1768 was highly conserved among virulent M. tb strains and mainly distributed as a secreted protein. Exposure to recombinant purified Rv1768 (rRv1768) induced apoptosis of bone marrow derived macrophages (BMDMs) but showed no dose-dependent manner. Regarding macrophage activation, significant higher levels of iNOS and pro-inflammatory cytokines (like IL-6 and TNF-α) were detected in rRv1768-challenged BMDMs, whereas arginase 1 (Arg1) expression was markedly decreased. Meanwhile, MHC-II expression and antigen presentation activity of BMDMs were also enhanced by rRv1768 stimulation, leading to significantly increased IFN-γ expression of CD4+ T cells isolated from H37Rv-infected mice. It is worthy to note that Rv1768-induced IFN-γ production of peripheral blood mononuclear cells (PBMCs) and Rv1768-specific immunoglobulins was specifically observed in H37Rv-infected mice, but not BCG-infected or normal mice. Analysis of clinical samples further revealed that Rv1768 had a higher sensitivity and specificity (91.38 % and 96.83 %) for tuberculosis diagnosis than the results obtained from clinical CFP10 and ESAT6 peptides-based enzyme-linked immunospot (ELISPOT) assay. The area under ROC curve of Rv1768 was 0.9618 (95% CI: 0.919-1.000) when cutoff value set as 7 spots. In addition, Rv1768-specific IgG and IgM also exhibited moderate diagnostic performance for tuberculosis. Our data suggest that Rv1768 is an antigen that strongly activates macrophages and has potential to serve as a novel ELISPOT-based TB diagnostic agent.